Midwifery Students’ Perspectives on Medical Daily Conversations in Ahmad Izzan’s English for Professionals - Astutie, Elma; Syamsara, Amaliya; Syahid, Abdul (CV. Ulil Albab Corp, 2025)
This study explores midwifery students' perceptions of Ahmad Izzan's textbook,